Pelestarian Cagar Budaya Melalui Fotografi Interior: Studi Visual Kapel Susteran FMM Regina Pacis Bogor - Selfano, Aldio; Fauzi, Muhammad (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the use of interior photography as a means to preserve and visually document the FMM Convent Chapel Regina Pacis in Bogor. The chapel is a historic site with significant artistic, spiritual, and architectural value, and has been officially recognized by the central government as a cultural heritage building. The importance of this research arises from the fact that the chapel is not included in the official publication of cultural heritage buildings in Bogor City that has been identified. Its absence from this publication indicates a lack of visual documentation and historical information necessary to support conservation efforts. Insufficient documentation increases the likelihood of losing architectural value should changes or damage occur in the future. To address this issue, the study seeks to produce interior photographic documentation that accurately and clearly represents the architectural identity of the chapel. This research employs a descriptive qualitative approach, consisting of interviews with the chapel’s management, direct on-site observations, and the development of an interior photography concept that considers spatial structure, perspective, and lighting. In this context, interior photography functions not only as an aesthetic medium but also as a preservation tool capable of storing long-term information.The resulting visual documentation is expected to serve as a valuable reference for managers, researchers, and local government authorities, while also encouraging the inclusion of the Regina Pacis Chapel in the official publication of cultural heritage buildings in Bogor City. In this way, the study contributes to strengthening cultural archives and supporting the preservation of historical architecture.